2004
DOI: 10.1007/s00276-003-0179-x
|View full text |Cite
|
Sign up to set email alerts
|

Topographic anatomy of the lingual nerve and variations in communication pattern of the mandibular nerve branches

Abstract: We made a thorough observation of the morphology and course of the lingual nerve (LN) and inferior alveolar nerve (IAN) to clarify their topographical relationships in the infratemporal fossa and in the paralingual area. Thirty-two Korean hemi-sectioned heads were dissected macroscopically and microscopically from a clinical viewpoint. On the 32 tracings on the radiograph, the average distance between the retromolar portion and the LN was 7.8 mm, and no case was found where the LN ran above the alveolar crest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 25 publications
4
62
0
4
Order By: Relevance
“…Due to analysing similar studies in the literature with this study, there are similarities between the mean values of vertical distance of the lingual nerve to the lingual crest of the mandible and the data of Pogrel et al 11 But some differ ences are found comparing Koreans 22 and our results. There are also some dif ferences in the mean values of horizon tal distance of the nerve to the lingual plate of the mandible with this study and the data of other studies.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Due to analysing similar studies in the literature with this study, there are similarities between the mean values of vertical distance of the lingual nerve to the lingual crest of the mandible and the data of Pogrel et al 11 But some differ ences are found comparing Koreans 22 and our results. There are also some dif ferences in the mean values of horizon tal distance of the nerve to the lingual plate of the mandible with this study and the data of other studies.…”
Section: Discussionmentioning
confidence: 58%
“…9 However, it was 15.5 mm in Korean adult cadavers. 22 In the present study, this vertical distance was 9.56 mm ± 5.28 mm in adult cadav ers in Cologne. Our results are more similar to adult Caucasians than Kore ans' values.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It is a thick nerve whose mean diameter is 2.56 mm (Karakas et al, 2007), and runs the infratemporal region and descends in search of the submandibular hiatus, through which it penetrates the paralingual space where it emits its terminal rami; at the height of the lower second molar, the lingual nerve makes a medial curve to surround the submandibular conduct and emit its terminal rami (Chan et al, 2010a). In its course, the lingual nerve can establish communications with the mylohyoid nerve, which completes its innervation and explains a percentage of aneasthetic failures (Behnia et al, 2000;Kim et al, 2004).…”
Section: Irrigation and Drainagementioning
confidence: 99%